2021
DOI: 10.3390/antibiotics10030265
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Viability of Lytic Phages and Their Potency against Multidrug Resistant Escherichia coli O177 Strains under Simulated Rumen Fermentation Conditions

Abstract: Preslaughter starvation and subacute ruminal acidosis in cattle are known to promote ruminal proliferation of atypical enteropathogenic Escherichia coli strains, thereby increasing the risk of meat and milk contamination. Using bacteriophages (henceforth called phages) to control these strains in the rumen is a potentially novel strategy. Therefore, this study evaluated the viability of phages and their efficacy in reducing E. coli O177 cells in a simulated ruminal fermentation system. Fourteen phage treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…[ 329 ], phiPA3 against Pseudomonas aeruginosa [ 330 ], phiRSL1 against Ralstonia sp. [ 331 ], vB_EcoM_10C2 and vB_EcoM_11B2 against E. coli O177 [ 332 ], and BPECO 19 against Escherichia coli O157:H7 [ 333 ], as well as R1-37 against Yersinia enterocolitica [ 334 ], have been determined. Several studies report the success of lytic phages against enterococci biofilms.…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%
“…[ 329 ], phiPA3 against Pseudomonas aeruginosa [ 330 ], phiRSL1 against Ralstonia sp. [ 331 ], vB_EcoM_10C2 and vB_EcoM_11B2 against E. coli O177 [ 332 ], and BPECO 19 against Escherichia coli O157:H7 [ 333 ], as well as R1-37 against Yersinia enterocolitica [ 334 ], have been determined. Several studies report the success of lytic phages against enterococci biofilms.…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%
“…The lack of additional therapeutic options and the ineffectiveness of traditional antibiotics in treating and managing harmful bacterial strains have recently accelerated the revival of phage therapy (Jaglan et al, 2022). In previous study, Montso et al (2021) demonstrated that lytic phages effectively reduced E. coli O177 cells under artificial rumen fermentation conditions, and could therefore be used as a biocontrol strategy in live cattle to reduce meat and milk contamination in slaughterhouses and milking parlors, respectively.…”
Section: Bacteriophagesmentioning
confidence: 99%